اشكالية الهوية وبناءالسيادة في دول الاتحاد الاوروبي - ممادي, علي (جامعة الوادي university el-oued)
"ملخص المذكرة: لقد تعرض الاتحاد الأوروبي في السنوات الماضية الى تفاقم أزمات الهوية، وأثرت تلك الأزمات الى وجود عدم استقرار في دول الاتحادالاوروبي،بالإضافة الى وجود تداعيات لتفكك الاتحاد الاوروبي بسبب أن الهويات الوطنية الأوروبية تختلف عن باقي الهويات في العالم،لأن الهوية الوطنية الأوروبية لديها تشبع في التعددية الثقافية من اللغة والقيم والعادات وغيها ،أي عدم وجود تجانس في الهويات الوطنية الأوروبية،كما أن هذه التعدديات في الهويات لايمكن أن تتجاهلها من مؤسسات الاتحاد الأوروبي لأنها ستخلق العديد من العوامل التي ستسبب عدة أزمات كالأزمات الاقتصادية مالية مثلا، وهذا ما خلق أزمة تكامل اقتصادي في دول الاتحاد الأوروبي في مثل اجراء سياسات التقشف الذي يقوم به الاتحاد وال>ي أثرا سلبا على العديد من القوميات ،أما على الشق الداخلي في دول الاتحاد الأوروبي فبروز الأحزاب اليمينية المتطرفة المطالبة بالانفصال على الاتحاد أو خروج إقليم ما عن الدولة الأم،حيث خلقة أزمات الهوية بيئة مساعدة الى ظهور الأحزاب الشعبوية واليمينية المتطرفة التي تعمل على بلورة الازمة ووضعها على الساحة الوطنية والأوروبية على الصعيد الخارجي فظهور أزمة الهوية كان مع مسألة الهجرة واللاجئين،حيث تشكل الهجرة بؤرة توتر في الهويات الوطنية، وهذا في مثال وصول عدد المسلمين في الاتحاد الاوروبي الى 50مليون مسلم وبنسبة تقدر بحوالي 5%،حيث أن اندماج المسلمون في أوروبا سيشكل ذوبان للهوية الوطنية الأوروبية. كما أن الدوافع التي أدت الى ظهور الحركات الانفصالية على الاتحاد وعلى الدول فهي عديدة ومختلفة في شتى المجالات فنجد في المجال الاقتصادي أسباب ظهور تلك الحركات كعدم وجود توزيع عادل لثروات سواء كان بين الاقليم ودولة أو بين سيادة الدولة والاتحاد الاوروبي،فعلى سبيل المثال نجد الحركة الانفصالية بأسكتلندا في حالة انفصالها على المملكة المتحدة فان الناتج القومي لإسكتلندا سيصبح ناتجها القومي مساوي لناتج القومي للمملكة ككل، أما في اقليم كتالونيا يشكل اقتصادها%20 من الاقتصاد الكلي في اسبانيا حالة الانفصال سوف يتحصل كل مواطن كتالوني 27 ألف يورو سنويا هذه العوامل الاقتصادية كانت الدوافع الحية لحركات الانفصال في أوروبا. كما أن العولمة لعبت دورا مهما في الحركات الانفصالية في دول اوروبا هذا نتيجة والتي أثرت على سيادة دول أوروبا،لان العولمة تهدف الى ذوبات سيادة الدول، وفي المقابل حفزت العولمة الحركات الانفصالية على الانفصال وذلك للاستفادة من اقتصاد تلك الاقاليم كتنشيط حركة الاسواقوسهولة التعامل مع تلك الاقاليم في الجانب السياسي. أما الحركة الانفصالية في كتالونيا هي ازمة متجذرة منذ عقود طويلة وتصاعدت على الساحة الوطنية والاقليمية،الى عدة عوامل تاريخية نتيجة اضطهاد الكتالونيين من السلطات الاسبانية خاصة في عصر فرانكو ومع منع اللغة الكتالونية من تداولها بين المواطنينالكتالونيين اصبح المحرك الرئيس للإقليمكتلونيا هو الهوية التي أصبح الاعتزاز بها واجب قومي ،ايضا العامل الاقتصادي في اسبانيا ساهم في ذلك حيث تعتبر من الدول التي تعرضت الى ازمة خانقة بعد ازمة اليورو،فكتالونيا لاتريد ان تكون اسبانيا عبئا عليها في ظل التخبطات التي تعصف بإسبانيا من بطالة وأزمات مالية،خاصة في ظل وجود اقتصاد قوي لكتالونيا سيجعل منها اقليم مزدهر غير بعيدة عن الدول المتقدمة. ان الحركة الانفصالية في كاتلونيامرتبطةأرتبطا وثيقا بالهوية الكتالونية والسيادة الاسبانية،فتصاعد الهوية ونمو الكتالونية سيؤثر على سيادة دولة اسبانيا،من خلال فقدان اسبانيا جزءا من اقليمها وسكانها،بالإضافة ان الانفصال سيؤثر على اسبانيا اقتصاديا وفقدان اسبانيا جزءا من مكوناتها. لذلك تسعى الحكومات الأوروبية على تقليل من حدة الحركة الانفصالية بكتالونيا وكما ان مؤسسات الاتحاد الاوروبي والدول تعمل على تقليل من شأن الأزمة وذلك خوفا من انتشارالحركات في الدول الاخرى،كما أن الاتحاد الاوروبي شدد بأن سيادة اسبانيا لاتمس، وان اسبانيا جزءا لايتجزأ من الاتحاد الاوروبي. ""Study summary In the past years, the European Union has been exacerbated by identity crises .which have led to an instability in the European Union. There are also repercussions for the disintegration of the European Union because European national identities differ from other identities in the world because it is saturated with pluralism Cultural, linguistic, values, customs and other ,it's up to the lack of homogeneity between these identities and which can not be ignored by the institutions of the European Union because it will create many factors that will cause several crises such as economic crises and financial . This has created a crisis of economic integration in the EU countries in the form of austerity measures carried out by the Union and negatively impacted many nationalities. internally of the European Union, there is the extreme right-wing parties who are demanding the secession of the Union or the departure of a region. The emergence of the identity crisis was the issue of migration and refugees, where migration is a source of tension in the national identities, and the emergence of the national unity, And This is in the example of the arrival of the number of Muslims in the European Union to 50 million Muslims by about 5%, and theirs integration in Europe represent a sort of melting of the European national identity. The motives that led to the emergence of separatist movements on the Union and the countries are many and different in various fields : economically, reasons for the emergence of such movements as the absence of a fair distribution of wealth, whether between the region and the state or between the sovereignty of the state and the European Union, In Scotland, in the event of its secession to the UK, the GNP of Scotland will be equal to the national product of the Kingdom as a whole. In Catalonia, its economy accounts for 20% of Spain's total economy. Economic factors were the driving forces of the movements of separation in Europe. Globalization has played an important role in the separatist movements in European countries. This has affected the sovereignty of the European countries because globalization aims at eliminating the sovereignty of countries. In turn, globalization has stimulated secessionist movements to secede and to benefit from the economy of these regions. Regions on the political side. The separatist movement in Catalonia is a crisis that has been rooted for many decades and has escalated on the national and regional levels to several historical factors as a result of the persecution of Catalans by the Spanish authorities, especially in the Franco era, and with the prohibition of the Catalan language from circulating among Catalan citizens. It has a national duty, also the economic factor in Spain contributed to this, where it is one of the countries that have been subjected to a crisis after the suffocation of the crisis of the euro, Catalonia does not want to be a burden on Spain in light of the shocks that hit Spain from unemployment and financial crises, A strong economy of Catalonia would make it a prosperous region not far from developed countries. The separatist movement in Catalonia is closely linked to Catalonian identity and Spanish sovereignty. The rise of identity and the growth of Catalonia will affect the sovereignty of the Spanish state by the loss of part of Spain and its population. Apartheid will affect Spain economically and Spain will lose some of its components. European governments are seeking to reduce the separatist movement in Catalonia and EU institutions and countries are working to reduce the crisis, fearing the spread of movements in other countries. The EU also stressed that Spain's sovereignty is not over and that Spain is an integral part of the European Union. "
م.س.ع.19
Keywords: "الهوية السيادة دول الاتحاد الاوروبي العولمة الحركات الانفصالبة "; "Identity Sovereignty European Union Separatist movements"